The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/j.2325-8012.2003.tb00554.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Demographics and Household‐Specific Price Indices on Consumption‐Based Inequality and Welfare: A Comparison of Spain and the United States

Abstract: Previous research has suggested that inequality is lower in Spain than in the United States when it is based on income. For the present article, both inequality and social welfare are examined, with household consumption expenditures used as a proxy for household welfare. For tractability, equivalence scales depended only on the number of people in the household. Household‐specific price indices were used to express the 1990‐1991 expenditure distributions in 1981 and 1991 winter prices. Our results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Thus, the study argues that the measurement of income per capita can overstate the level of deprivation. In line with our results, Garner et al (2002), while discussing the consumption-based inequality and welfare of Spain and USA, argued the importance of household demographic characteristics and equivalence scale adjustments for international comparisons. It was showed that adjustment helps to overcome a bias causing an overestimation of adults’ and an underestimation of children’s needs-based equivalence weights (Borah et al , 2016; Blaylock, 1991).…”
Section: Resultssupporting
confidence: 89%
“…Thus, the study argues that the measurement of income per capita can overstate the level of deprivation. In line with our results, Garner et al (2002), while discussing the consumption-based inequality and welfare of Spain and USA, argued the importance of household demographic characteristics and equivalence scale adjustments for international comparisons. It was showed that adjustment helps to overcome a bias causing an overestimation of adults’ and an underestimation of children’s needs-based equivalence weights (Borah et al , 2016; Blaylock, 1991).…”
Section: Resultssupporting
confidence: 89%
“…The destination SEP measure is derived from Wave 5 personal income, also divided into quintiles. To account for individuals’ household size at Waves 1 and 5, we adjusted household and personal income based on equivalence scales (income/(household size) 0.5 ) used in the previous research for the United States ( 52 , 53 ). We estimated individuals’ intergenerational income mobility as the difference between Waves 1 and 5 income quintiles.…”
Section: Methodsmentioning
confidence: 99%
“…Household income was adjusted to household size using an equivalence scales method: income/(household size) 0.5 . Tertiles of household income were used when analyses were stratified by this variable.…”
Section: Methodsmentioning
confidence: 99%